ANALISIS HAMBATAN BELAJAR PESERTA DIDIK PADA PROSES PEMBELAJARAN DI KELAS IV SD NEGERI 2 SOKARAJA BANJARNEGARA - Dewi Irma Ardiningrum; Ana Andriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses learning barriers of students in the learning process in grade IV of SD Negeri 2 Sokaraja Banjarnegara. The main focus of the study includes cognitive, behavioral, and environmental aspects that affect the learning process in the classroom. The method used is a qualitative approach with observation, interview, and documentation techniques. The results of the study showed that students had difficulty in understanding memorization material, reading story problems, and constructing sentences when writing. Students' concentration was low, they were easily distracted by their surroundings, and tended to be passive. Students were unable to respond optimally to teacher explanations. Several students showed hyperactive behavior, one of whom was identified as having asperger syndrome. This study aims to identify the forms of learning barriers experienced by students and the teacher's efforts to overcome these barriers in the classroom environment. Learning media are limited to pictures, videos, and textbooks. The learning methods applied are lecture-based and less varied. The learning environment at home is less supportive, students do not get tutoring because they live with their grandparents. Dependence on gadgets is high, repetition of material at home is rarely done. School facilities are minimal, there are no special programs for students with learning disabilities. Teachers have tried to establish personal communication, but it has not had a significant impact. Learning evaluations show that most students have not been able to solve problems independently. The learning process is not running optimally and has not answered the learning needs of all students.